(untitled) (Berlin, 2006)
This book constitutes the refereed proceedings of the 7th Pacific Rim Conference on Multimedia, PCM 2006, held in Hangzhou, China in November 2006. The book consists of 116 revised papers presented which were carefully reviewed and selected from a total of 755 submissions. The papers cover a wide range of topics, including all aspects of multimedia, both technical and artistic perspectives and both theoretical and practical issues. Fields addressed are multimedia processing and retrieval, multimedia system support and networking, multimedia security, as well as multimedia tools, end-systems and applications
Tôpô đại cương
Keywords: Multimedia systems,Hệ thống đa phương tiện